PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI (Studi Pada PT. Telekomunikasi Indonesia, Tbk Wilayah Telkom Pekalongan) - Pratiwi, Annisa; Darmastuti, Ismi (Faculty of Economics and Business Diponegoro University, 2014)
The research aims to examine and analyze the influence of motivation and work discipline toward performance of employee in PT Telekomunikasi Indonesia Tbk. Witel Pekalongan. This research was a sample of 56 of the 125 employees of PT Telekomunikasi Indonesia Tbk. Witel Pekalongan. Samples was taken by Convenience sampling. The analysis used is multiple regression. By using signification limits about 0,05.Based on data calculation result of cost analysis used, obtained regression equality of : Y = 0,491X1 + 0,194X2 Analysis result demonstrates that motivation have a positive and significant influence between motivation to employee performance. By significant value about 0,02 (less than 0,05). Therefore, hypothesis which stated that motivation have influence to employee’s work could be accepted. There was no significant influence between work discipline to employee performance, by significant value 0.199 (greater than 0.05). Simultaneously both motivation and work dicipline have positive and significant influence to employee’s performance by f value about 18,729 (more than 0.05), therefore obtained signification value 0,000.